MANAJEMEN KEPALA SEKOLAH DALAM MEWUJUDKANBUDAYA RELIGIUS DI SEKOLAH DASAR ISLAM TERPADU AR-RAHMANPALANGKI - Mus Muliadi; Himyar Pasrizal; Arpinus Arpinus (IAIN Batusangkar, 2019)
The purpose of this study was to find out how principals in applying religious culture and to find out the forms of religious culture that were applied at SDIT Ar Rahman Palangki. The type of research used is descriptive qualitative. The research informants were five people. Data collection tools are researchers as key instruments and supporting instruments are interview guidelines, observation guidelines, field notes, and mobile phones. Data collection techniques are participatory observation, in-depth interviews and documentation studies. The data analysis technique uses an interactive model proposed by Miles and Huberman, namely collecting data, reducing data, presenting conclusions data. The results of the study show that Principal Management in realizing religious culture starts from planning (daily programs, weekly programs, quarterly programs, and semester programs). Then organizing (division of tasks). Furthermore, the implementation, namely tahfiz, memorization of hadith, azan, dhikr, prayer, sunnah fasting, dhuha prayer, midnight prayer congregation, open together and MABIT. Furthermore, supervision, supervision or evaluation carried out is a routine meeting every month and through the student's daily personal books.